Circulating Levels of Glial Cell Line-Derived Neurotrophic Factor (GDNF) in Schizophrenia: a systematic review and meta-analysis - Omran Davarinejad; Saeid Komasi; Mohammad-Taher Moradi; Farzaneh Golmohammadi; Maryam Bahrami; Hamed Esmaeil Lashgarian; Masumeh Jalalvand; Sara Hookari; Fatemeh Kazemisafa (BMC Psychiatry)
Abstract Background Glial cell line-derived neurotrophic factor (GDNF) has emerged as a potential biomarker for schizophrenia (SCZ). However, GDNF levels remain unclear in affected individuals compared to healthy controls. Therefore, we aimed to calculate a pooled estimate of GDNF levels in patients with SCZ in comparison with healthy controls. Methods A systematic search was performed in PubMed, Scopus, Web of Science, and Science Direct for published studies from the first date available up to 17 June 2024. Twelve studies (n = 817 patients and 691 healthy controls) were included in the meta-analysis. Subgroup analyses and meta-regression were performed, addressing heterogeneity and publication bias. Results Random-effects estimates (d = –0.80, p < 0.001) of the present meta-analysis revealed a significant mean difference in GDNF levels between SCZ patients and healthy controls. Subgroup analyses indicated that the standardized mean difference of GDNF was larger in European samples (d = –1.01, p ≤ 0.001) than in the Asian population (d = –0.61, p = 0.011). Non-medicated SCZ patients (d = –1.08, p ≤ 0.001) exhibited lower GDNF levels than those on medication (d = – 0.70, p = 0.004). Additionally, patients with a disease duration of ≥ 10 years showed lower levels of GDNF (d = –0.93, p = 0.058 versus d = –0.82, p = 0.002). Conclusions The findings suggested that GDNF may be a promising biomarker and therapeutic target for schizophrenia. Future research should focus on elucidating the mechanisms underlying altered GDNF levels and exploring its implications for treatment strategies.